High‐Frequency Seismic Events on Mars Observed by InSight. Issue 2 (23rd February 2021) - van Driel, Martin; Ceylan, Savas; Clinton, John F.; Giardini, Domenico; Horleston, Anna; Margerin, Ludovic; Stähler, Simon C.; Böse, Maren; Charalambous, Constantinos; Kawamura, Taichi; Khan, Amir; Orhand‐Mainsant, Guenolé; et al.
Abstract: The seismometer deployed on the surface of Mars as part of the InSight mission (In terior Exploration using S eismic I nvestigations, G eodesy and H eat T ransport) has recorded several hundreds of marsquakes in the first 478 sols after landing. The majority of these are classified as high‐frequency (HF) events in the frequency range from approximately 1 to 10 Hz on Mars' surface. All the HF events excite a resonance around 2.4 Hz and show two distinct but broad arrivals of seismic energy that are separated by up to 450 s. Based on the frequency content and vertical‐to‐horizontal energy ratio, the HF event family has been subdivided into three event types, two of which we show to be identical and only appear separated due to the signal‐to‐noise ratio. We show here that the envelope shape of the HF events is explained by guided Pg and Sg phases in the Martian crust using simple layered models with scattering. Furthermore, the relative travel times between these two arrivals can be related to the epicentral distance, which shows distinct clustering. The rate at which HF events are observed varies by an order of magnitude over the course of one year and cannot be explained by changes of the background noise only. The HF content and the absence of additional seismic phases constrain crustal attenuation and layering, and the coda shape constrains the diffusivity in the uppermost shallow layers of Mars. Plain Language Summary: The high‐frequency events are the most commonly observed class of marsquakes by the InSight mission. As the frequency content and signal shape over time is different from seismic events (i.e., events that excite elastic waves traveling in the subsurface such as earthquakes, impacts, or explosions) observed both on Earth and the Moon, these were not immediately recognized as signals of seismic origin. This paper shows that these signals can be explained by distant shallow small quakes together with wave propagation effects in the Martian crust. This interpretation opens the possibility to use these signals to probe the material properties of the crust and raises the question which physical process causes these events. Key Points: InSight's seismometers have recorded several hundreds of events at frequencies between 1 and 10 Hz The envelopes of these events can be explained by seismic waves guided in the crust over significant distances This observation helps to constrain the elastic properties of the shallow structure